An active fixation quadripolar left ventricular lead for cardiac resynchronization therapy with reduced postoperative complication rates. (11th January 2022) - Robertson, Calum; Duffey, Owen; Tang, Pok‐Tin; Fairhurst, Natalie; Monteiro, Cristiana; Green, Peregrine; Grogono, Joanna; Davies, Mark; Lewis, Andrew; Wijesurendra, Rohan; Ormerod, Julian; Gamble, James; et al.
Abstract: Background: The rate of left ventricular (LV) lead displacement after cardiac resynchronization therapy (CRT) remains high despite improvements in lead technology. In 2017, a novel quadripolar lead with active fixation technology became available in the UK. Methods: This was a retrospective, observational study analyzing device complications in 476 consecutive patients undergoing successful first‐time implantation of a CRT device at a tertiary center from 2017 to 2020. Results: Both active ( n  = 135) and passive fixation ( n  = 341) quadripolar leads had similar success rates for implantation (99.3% vs. 98.8%, p  = 1.00), although the pacing threshold (0.89 [0.60–1.25] vs. 1.00 [0.70–1.60] V, p  = .01) and lead impedance (632 [552–794] vs. 730 [636–862] Ohms, p  < .0001) were significantly lower for the active fixation lead. Patients receiving an active fixation lead had a reduced incidence of lead displacement at 6 months (0.74% vs. 4.69%, p  = .036). There was no significant difference in the rate of right atrial (RA) and right ventricular (RV) lead displacement between the two groups (RA: 1.48% vs. 1.17%, p  = .68; RV: 2.22% vs. 1.76%, p  = .72). Reprogramming the LV lead after displacement was unsuccessful in most cases (successful reprogramming: Active fix = 0/1, Passive fix = 1/16) therefore nearly all patients required a repeat procedure. As a result, the rate of intervention within 6 months for lead displacement was significantly lower when patients were implanted with the active fixation lead (0.74% vs. 4.40%, p  = .049). Conclusion: The novel active fixation lead in our study has a lower incidence of lead displacement and re‐intervention compared to conventional quadripolar leads for CRT.